Bioethics and health in times of climate crisis: an analysis of the book "Climate change: let’s act from the Health sector" - García, Mario A. (Revista Gregoriana de Ciencias de la Salud, 2025)
The book "Climate Change: Let’s Act from the Health Sector" by Eugenio Radamés Borroto Cruz and Patricia María Jiménez López, published in 2024 by Editorial San Gregorio (Portoviejo, Ecuador), is a fundamental work that connects the ethical, scientific, and practical challenges of climate change with public health. Divided into eight chapters, this publication combines scientific rigor and ethical sensitivity to emphasize the urgency of addressing climate change from the health sector and other interconnected areas. From the introduction, the authors highlight the severity of climate change as the principal risk to public health in the 21st century. This is a multidimensional phenomenon with implications ranging from heat waves and vector-borne diseases to food insecurity and forced migrations.